THE CONCEPT OF SELF DEVELOPMENT AT SDN PONDOK 1 BABADAN IN DEVELOPMENT OF COMMUNICATIONS TECHNOLOGY 4.0 - Amin kurniawan; Idris Akbar Pramono (PROGRAM STUDI ILMU KOMUNIKASI, 2023)
This study is important for explaining self-development in dealing with the development of communication technology in the 4.0 era. It is proven that the development of communication technology can change the pattern of communication in human life. However, humans should not be governed by technology, but humans are essentially the regulators of technology. The problem is where is the human position in the development of communication technology. This concept needs to be understood so that we don't get caught up in the development of communication technology in the 4.0 era. This study uses the ethnomethodological method to find forms of self-readiness in dealing with developments in communication technology. Data was collected through observation, documentation and literature review, then analyzed against the documentation. This study uses an naturalistic communication approach, to explain the communication relationship that is formed within oneself with the development of communication technology. The results explain that self-development becomes potential and self-readiness, which every human being must have in dealing with the development of communication technology. The development of communication technology can group humans into two positions, namely technology builders or technology consumers. Adjusting to our position as consumers can lead us to easy and practical communication, such as the benefits of the internet, the benefits of smartphones, television and so on. The development of communication technology is a global development that cannot be dammed or anticipated. Humans need to adapt themselves to technological developments, in order to understand them